2006
DOI: 10.1002/ffj.1749
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Hypericum hirsutum L.

Abstract: The essential oil of Hypericum hirsutum was analysed for the first time. Twenty-seven components were identified. The non-terpene compounds had the highest contribution (46.6%). A low monoterpenes content (1.3%) characterized the oil. The major constituents were n-undecane (32.2%), patchoulene (11.8%) and caryophyllene oxide (9.3%), which are not significantly represented in the essential oils of other species of the genus Hypericum examined. Copyright

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…A low monoterpenes content (1.3 %) characterized the oil. The major constituents were n-undecane (32.2 %), patchoulene (11.8 %) and caryophyllene oxide (9.3 %), which are not significantly represented in the essential oils of other species of the genus Hypericum examined 30 .…”
Section: Resultsmentioning
confidence: 99%
“…A low monoterpenes content (1.3 %) characterized the oil. The major constituents were n-undecane (32.2 %), patchoulene (11.8 %) and caryophyllene oxide (9.3 %), which are not significantly represented in the essential oils of other species of the genus Hypericum examined 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Only a small part of the genus has been studied, and the chemical content of approximately threequarters of Hypericum species has not been surveyed (Karioti and Bilia 2010). However, some authors have found that H. maculatum synthesizes and accumulates hypericin (Bagdonait_ e and Kazlauskas 2006; Mártonfi et al 2006), essential oils and flavonoids (Gudžić et al 2007;Smelcerovic et al 2007) in amounts close to those detected for H. perforatum. Hypericum hirsutum L. (hairy St. John's wort) is another less well-studied species that may synthesize moderate quantities of hypericins and hyperforin (Kusari et al 2009;Smelcerovic et al 2006) as well as appreciable amounts of essential oils ).…”
Section: Introductionmentioning
confidence: 94%
“…Dried and pulverized aerial parts of the plant (100 g) were hydrodistilled for 2.5 h using a Clevengertype apparatus. [14][15][16] Identification procedure…”
Section: Experimental Plant Materialsmentioning
confidence: 99%